Analysis of Incentives, Monitoring, Motivation, and Employee Performance at the Office of Public Housing, Residential Areas and Transportation of Mojokerto Regency - adi mahendarto; Ernani Hadiyati; Abdul Halim (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives - The aim of the study was to identify and analyze the effect of incentivesand monitoring on employee performance through work motivation at theDepartment of Public Housing, Residential Areas and Transportation, MojokertoRegency.Design/Methodology/Approach – The sampling technique used is the saturatedsample technique, in which the entire population is sampled, totaling 85 people withthe status of State Civil Apparatus (ASN) (excluding leaders) of the Public Housing,Settlement Areas and Transportation Office (DPRKP2) Mojokerto Regency. Theprimary data collection method uses a questionnaire while the secondary datacollection uses the literature study method. Data analysis techniques in this studyused instrument tests, path analysis tests, and classical assumption tests.Findings - Based on the results of the research and discussion, it is concluded thatincentives can increase work motivation and employee performance, supervision canincrease work motivation and employee performance, motivation and incentives can directly increase employee performance. The discussion of the findings is explainedin the research findings.